2007
DOI: 10.1111/j.1600-0447.2007.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of mental disorder in attacks on European politicians 1990–2004

Abstract: A greater awareness of the link between delusional fixations on public figures and subsequent attacks could aid prevention. Equally importantly, recognition would encourage earlier intervention in people who, irrespective of whether they eventually attack, have delusional preoccupations which ruin their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 10 publications
10
101
0
Order By: Relevance
“…The warning behavior, directly communicated threat, is arguably the least important in a threat assessment, and least frequent, among the acts of targeted violence we are considering: public figure attacks and assassinations, adult and adolescent mass murders, and school shootings. This point is empirically underscored by two studies in the US and Europe James et al, 2007) which found that among an aggregated sample of 58 public figure attackers and assassins over the past several decades, not one communicated a direct threat to law enforcement or the target before the attack. However, direct threats do occur, and, particularly in the context of the "intimacy effect" (Calhoun & Weston, 2003), i.e., direct threats are more predictive of violence the more intimate the relationship between the target and the perpetrator, they should be taken very seriously (Rosenfield, Fava, & Galietta, 2009).…”
Section: Warning Behaviorsmentioning
confidence: 91%
See 1 more Smart Citation
“…The warning behavior, directly communicated threat, is arguably the least important in a threat assessment, and least frequent, among the acts of targeted violence we are considering: public figure attacks and assassinations, adult and adolescent mass murders, and school shootings. This point is empirically underscored by two studies in the US and Europe James et al, 2007) which found that among an aggregated sample of 58 public figure attackers and assassins over the past several decades, not one communicated a direct threat to law enforcement or the target before the attack. However, direct threats do occur, and, particularly in the context of the "intimacy effect" (Calhoun & Weston, 2003), i.e., direct threats are more predictive of violence the more intimate the relationship between the target and the perpetrator, they should be taken very seriously (Rosenfield, Fava, & Galietta, 2009).…”
Section: Warning Behaviorsmentioning
confidence: 91%
“…If near-lethal approachers are included, the direct threat frequency increases from 0 to 7%. In a study of attackers of western European politicians (James et al, 2007), 46% of the attacks (N = 24) were preceded "by obvious and often flamboyant warning behaviors in the form of threatening or bizarre communications to politicians, public figures, or police forces" (p. 342). This study, however, did not specifically focus upon the percentage of those attackers who leaked their intent to attack to a third party.…”
Section: Research On Leakagementioning
confidence: 99%
“…On the other hand, Hiday (1995) and Scott and Resnick (2006) argue those who are mentally ill to be no more dangerous than the general population. These issues have also not been applied in a systematic sense to the types of violence associated with terrorist activity apart from James et al (2007), who found that mentally ill perpetrators of attacks on European politicians engaged in higher levels of violence.…”
Section: Irrationality and Violencementioning
confidence: 99%
“…Given my involvement in the observation unit described above, I am a biased observer and therefore I leave it to readers to make their own evaluation of the importance of the problem described by James et al (5) and the validity of the solution proposed by James which the London Mail on Sunday has taken exception to. It would be good to see some correspondence from psychiatrists on their views about leaving psychotic patients to wander the streets without the benefits of mental health care, and to see if there are other proposals which would be more effective and ⁄ or more palatable in the prevention of political assassinations, assuming this is a task of sufficient merit to be undertaken anyway.…”
Section: Contemporary Attitudes Perhaps?mentioning
confidence: 99%